A walk along with Jean.Jacques Rousseau An essay - Stanislaus Stefaniak, Andrea (Universidad Femenina del Sagrado Corazón (UNIFÉ), 2017)
This article is about analyzing very briefly, using two excerpts of the “Confessions”, the role that walks play in the thought of Jean-Jacques Rousseau (1712-1778), and hence, to share with the students of our institution an epoch-making author in modern European thought. For many authors the experience of a walk is a metaphor for thought, but in Rousseau it occupies a privileged position in the philosophical approach, due to its physical aspect as an existential experience.